ANALISIS SISTEM AKUNTANSI ANGGARAN BELANJA DANA INFRASTRUKTUR DI DESA TULUNG AGUNG PELALAWAN - Widiyanti, Widiyanti (International Journal of Business and Information Technology, 2021)
Based on the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 113 of 2014 concerning Village Financial Management, "Village Spending includes all expenditures from village accounts which are village obligations within 1 (one) fiscal year which will not be repaid by the village and are used to fund the implementation of village authority. This study uses secondary data sources, data collection methods by means of observation. The object of this research is Tulung Agung Village in Pelalawan Regency. Tulung Agung Pelalawan Village in implementing the accounting system for the budget for infrastructure funds still uses a manual system, namely inputting data by recording in a ledger without discipline in compiling and attaching a memorandum file. So, it requires a lot of energy and time in the recording process and a big risk in bookkeeping errors. Based on the infrastructure budget accounting system currently running in Tulung Agung Village, it is proposed that the Infrastructure Fund Budget accounting system uses an application, namely Microsoft Access.